Educational quality assurance: The impact of policy on student learning outcomes. - Andrianti, Sarah; Ming, David (Universitas Jambi, Indonesia, 2026)
This study examines how schools for students with special needs maintained quality assurance practices during the COVID-19 pandemic. It examines the stages of QA planning, implementation, evaluation within the school accreditation process, and how school leaders viewed QA as a form of institutional accountability during a period of educational disruption. The analysis refers to the standards established by the National Accreditation Board for Schools/Madrasah which focuses on four major aspects: graduate competency, teaching and learning processes, teacher qualifications, and school management. As the demand for globally competitive education continues to grow, the Indonesian government has encouraged educational institutions to strengthen their accreditation systems. This has raised important issues, including the role of national accreditation bodies, alignment between local and international quality assurance (QA) standards, and recognition of accreditation outcomes across institutions. The study found that schools relied heavily on collaboration among teachers, principals, parents, and other stakeholders to maintain educational quality during the pandemic period.